Increasing Cell Seeding Density Improves Elastin Expression and Mechanical Properties in Collagen Gel‐Based Scaffolds Cellularized with Smooth Muscle Cells. Issue 3 (17th June 2018) - Camasão, Dimitria B.; Pezzoli, Daniele; Loy, Caroline; Kumra, Heena; Levesque, Lucie; Reinhardt, Dieter P.; Candiani, Gabriele; Mantovani, Diego
Abstract : Vascular tissue engineering combines cells with scaffold materials in vitro aiming the development of physiologically relevant vascular models. For natural scaffolds such as collagen gels, where cells can be mixed with the material solution before gelation, cell seeding density is a key parameter that can affect extracellular matrix deposition and remodeling. Nonetheless, this parameter is often overlooked and densities sensitively lower than those of native tissues, are usually employed. Herein, the effect of seeding density on the maturation of tubular collagen gel‐based scaffolds cellularized with smooth muscle cells is investigated. The compaction, the expression, and deposition of key vascular proteins and the resulting mechanical properties of the constructs are evaluated up to 1 week of maturation. Results show that increasing cell seeding density accelerates cell‐mediated gel compaction, enhances elastin expression (more than sevenfold increase at the highest density, Day 7) and finally improves the overall mechanical properties of constructs. Of note, the tensile equilibrium elastic modulus, evaluated by stress‐relaxation tests, reach values comparable to native arteries for the highest cell density, after a 7‐day maturation. Altogether, these results show that higher cell seeding densities promote the rapid maturation of collagen gel‐based vascular constructs toward structural and mechanical properties better mimicking native arteries. Abstract : Vascular smooth muscle cell seeding density strongly affects the maturation of collagen gel‐based vascular wall models. Increasing cell density in the collagenous matrix accelerates the construct compaction process and influences the cell‐mediated remodelling, especially boosting the expression and deposition of elastin. Finally, improved mechanical properties are obtained, approaching those of native arteries already after one week of static maturation.